Modification of concentration-response curves to inhaled methacholine after the pollen season in subjects with pollen induced rhinitis. Issue 7 (July 1994) - Prieto, L; López, M; Bertó, J M; Peris, A
Abstract : BACKGROUND–The effect of cessation of exposure to pollen on the concentration-response curves to inhaled methacholine was investigated. METHODS–Methacholine inhalation challenges (up to 200 mg/ml) were performed in 13 non-asthmatic patients with grass and/or Parietaria pollen-induced rhinitis during the pollen season, and one and four months after it. Concentration-response curves were characterised by their PC20, position, and plateau. RESULTS–Geometric mean methacholine PC20 increased from 6.4 mg/ml during the pollen season to 28.2 mg/ml and 54.9 mg/ml one and four months after the end of season, respectively. The mean (SE) level of the plateau decreased from 30.5 (4.3%) in the pollen season to 23.3 (3.7)% and 20.1 (3.3)% one and four months after the end of pollen season, respectively. Although the methacholine concentration that produced 50% of the maximal response increased from 2.9 mg/ml to 4.3 mg/ml and 6.0 mg/ml, the differences were not significant. CONCLUSIONS–In non-asthmatic patients with pollen-induced rhinitis cessation of exposure to pollen is associated with significant modifications in the methacholine threshold value and level of plateau, and with a small shift in the concentration-response curves to the right.